AUTENTIFIKASI DAN INFILTRASI DALAM TAFSIR ISHĀRĪ - Husna, Rifqatul (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2021)
The ishārī interpretation is one of the style or form in the tafsir studies. On the one hand, ishāri was considered to have a positive impact on the interpretation of the al-Qur’an and on the other hand, it was considered a deviant kind of interpretation from al-maqāsid al-shar’iyyah or even contrary to the al-Qur’an and hadīth as the main source in interpreting the al-Qur’an. Therefore, scholars make provisions, criteria, and requirement in interpretation. The mufassir classifies what is considered the main (al-asīl) or basis in an interpretation, and which is considered as abuses (al-dakhīl) in an interpretation. From this academic problem, the discipline of al-asīl wa al-dakhīl fi al-tafsīr was emergent. This research aims to aim to discovere out meeting point the ishāri interpretation, whether it is true or worthy of being considered as al-dakhīl in interpretation or is it necessary to reconstruct the definition, type, or division in the knowledge of al-asīl and al-dakhīl? This study uses the content analysis method so that discussions and conclusions can be traced so that it can produce a neat and orderly conclusion, which in turn results in a conclusion that the ishārī interpretation will be considered and categorized as al-asīl if it meets several conditions: a) the interpretation does not contradict the meaning of z}ahir the end of the verse, b) the interpretation must not contradict reason and sharī'ah, and c) between the interpretation and the interpretation interpreted there is a relationship and correlation.